Pre-Service Teachers' Perspectives on the Effectiveness of the READABLE App for Improving Reading Comprehension - Jannah, Miftahul Jannah; Siti Ismahani (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
Advancements in technology have significantly impacted literacy instruction, particularly in improving reading comprehension. Despite the growing number of digital reading platforms, many learners, including students in educational settings, continue to struggle with deep comprehension. The READABLE app, a digital reading platform that offers simplified English stories, was developed to address these challenges. This study aimed to examine the effectiveness of the READABLE app in enhancing pre-service teachers' ability to support reading comprehension. Data were collected through questionnaires, observations, and semi-structured interviews. Thematic analysis revealed that pre-service teachers held highly positive perceptions of the READABLE app. Features such as interactivity, personalized materials, and automatic feedback were considered effective in increasing student engagement and learning outcomes. The app was also viewed as helpful for supporting students' understanding of texts by offering content tailored to their reading levels. Its engaging learning environment motivated students to read regularly, contributing to gradual and sustainable skill development. As such, the READABLE app is regarded as a valuable tool in supporting English language learning, especially for improving overall reading comprehension